Preclinical testing of a novel pericardial left ventricular assist device (PALVAD). (26th April 2021) - Premawardhana, ADPE; Lodge, A; Sachdev, S; Karamanavi, E; Kotecha, D; Lees, JE; Mariscalco, G; Rothman, A; Gunn, J; Samara-Ratna, P; Adlam, D
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): British Heart Foundation Background: Cardiogenic shock (CS) complicates 8% of acute myocardial infarctions and has a short-term mortality approaching 50%. Traditional mechanical circulatory support (MCS) have significant adverse event profiles related to their position within the circulation. PALVAD is an extra circulatory MCS designed to be implanted percutaneously. The dual balloon system provides cardiac support whilst sitting in the space between the pericardium and left ventricular (LV) free wall. The actuator (ACT) balloon augments CO through ECG gated LV systolic compression and the positioning balloon sits against the pericardium dissipating this force. Methodology: Non-recovery experiments were conducted in eleven 40k-60g pigs. A percutaneous coronary balloon occlusion model was initially used (n = 3) following which an Esmolol infusion model (n = 8) was used due to increased stability when titrating for a low cardiac output state . A Millar catheter was placed in the LV for simultaneous pressure and volume measurements and a Transonic flow probe was placed around the internal carotid. The device was inserted percutaneously and operated for alternating on/off periods. The device was inserted into a saline perfused cadaver following which CT and MRI imaging was undertaken. CT images were reconstructed three dimensionally and analysed. Results: PAL-VAD had a significant impact across all parameters with a mean increase of 42% ± 16.1 in CO, 42% ± 17.3 in stroke volume, 20% ± 15.5 in pressure and a 30% ± 18.5 in flow and a mean device actuation of 48mins. Cadaveric imaging confirmed appropriate device dimensions for human anatomy and a 32% reduction in LV volume was seen with ACT balloon inflation. Conclusions: PALVAD performance in during a low CO state is promising. Recovery experiments, including histology assessment, are planned to further evaluate safety and efficacy with longer-term use.